2019
DOI: 10.1111/sms.13385
|View full text |Cite
|
Sign up to set email alerts
|

Low energy availability, menstrual dysfunction, and impaired bone health: A survey of elite para athletes

Abstract: Introduction: The Female Athlete Triad (Triad) is a syndrome describing three interrelated conditions: low energy availability (LEA), menstrual dysfunction, and low bone mineral density (BMD). Relative Energy Deficiency in Sport (RED-S) expands the Triad to include multiple physiologic consequences of LEA in both sexes. The purpose of this study is to determine the prevalence of factors associated with the Triad/RED-S in an elite para athlete population. Methods: Athletes were U.S. elite para athletes training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 26 publications
0
59
2
Order By: Relevance
“… 77 The lack of prognosis of DE in male elite athletes represents another knowledge gap, since only two conflicting studies on the prognosis of weight cycling among male athletes competing in weight-class sports were found. 81 82 Moreover, the only study on DE in male elite para athletes found similar rates of DE among male elite non-para athletes, 72 although they may be at greater risk of DE consequences. 77 …”
Section: Discussionmentioning
confidence: 99%
“… 77 The lack of prognosis of DE in male elite athletes represents another knowledge gap, since only two conflicting studies on the prognosis of weight cycling among male athletes competing in weight-class sports were found. 81 82 Moreover, the only study on DE in male elite para athletes found similar rates of DE among male elite non-para athletes, 72 although they may be at greater risk of DE consequences. 77 …”
Section: Discussionmentioning
confidence: 99%
“…The risk of low EA has been investigated using surrogate markers or self-reported symptoms of low EA in various athlete populations including elite para-athletes [34], adolescent/young adult [35,36] and Olympic athletes [40], female sprinters [41], male jockeys [39] and recreationally active individuals [33,37], and ranges from 14% to 63% ( Table 3). The largest cross-sectional study investigating self-reported health and performance outcomes linked to low EA and RED-S [5] placed emphasis on including body systems beyond reproductive function and bone health such as metabolic, haematological, psychological and cardiovascular health and gastrointestinal function.…”
Section: Low Energy Availability Riskmentioning
confidence: 99%
“…The EDE-Q covers risk factors including behaviours associated with DEI and EEEtendencies that lead towards intentional LEA. The EDE-Q has been used in adults and adolescents of both sexes [42,43], in athletic populations and elite para athletes [22,44]. It was used as a surrogate marker for LEA, and measured Triad components in female athletic populations [45,46].…”
Section: Eating Disorder Examination Questionnaire (Ede-q)mentioning
confidence: 99%